Canopy temperature and heat use efficiency of spring maize under modified soil microenvironment - Majumder, Debjyoti; Kingra, P.K.; Kukal, S.S. (Annals of Agricultural Research, 2016)
A field experiment was conducted to assess the canopy temperature and heat use efficiency of maize (var. PMH-7) under modified soil micro environment during spring 2014 at the Research Farm, Punjab Agricultural University, Ludhiana. The experiment was laid out in factorial randomized block design comprising three irrigation levels (IW/CPE = 1.25 (I1), 1.0 (I2) and 0.75 (I3)) and four manuring treatments (surface manurng (S), sub-surface manuring (DF), digging alone (D) and control (C). Higher canopy temperature was observed under the I3 followed by I2 and I1, whereas under manuring treatments, higher temperatures were observed under control (C), followed by digging (D), surface (S) and sub-surface manuring (DF), respectively. Crop took 127 days to complete its life cycle and accumulated 5062.3°C day growing degree days (GDD), 45795.3°C day hour heliothermal units (HTU) and 64664.7°C day hour photothermal units (PTU). The regression analysis depicted positive relation of heat use efficiency with maximum leaf area index (R2 = 0.61), dry matter production (R2 = 0.97) and grain yield (R2 = 0.55) under different irrigation and manuring treatments. The regression analysis between canopy temperature and grain yield under different treatments showed negative relation indicating a decrease in grain yield of maize by 2.8 q/ha with increase in canopy temperature by 1°C. The study highlights the negative impact of global warming on crop productivity and significance of microclimatic modifications viz. irrigation scheduling and subsurface manuring in managing canopy temperature and heat use efficiency of spring maize under changing climatic conditions.